Intelligence Analysis Method of Automation Control System Archive Database for controlling Hot Blast Stove Block - Koyfman, O. O.; Simkin, O. I.; Serdiuk, K.; Сімкін, О. І.; Койфман, О. О. (CEUR Workshop Proceedings, 2020)
In automated process control systems the data from the archive data-base are used in most cases in a graphic form for analyzing the technological process history. Frequently, the controlling of а hot blast stove block occurs in the conditions of incomplete information. The method of data mining of the ar-chive database was developed and implemented in the form of computer pro-grams to obtain new interconnections between the main technological parame-ters of the blast air heating process in a hot blast stove block. The developed al-gorithm allows to determine the functional dependence of the base parameter on two other parameters with fixing the third parameter in a certain range. The ob-tained analytical dependencies allow us to make decisions about changes in control algorithms for a hot blast stove block.
Keywords: Intelligence analysis; data mining; method; approximation; hot blast stove; HBS; flow-chart; computer application